Padrão de sono e atividade física ao longo do ano na estação antártica comandante Ferraz - GARCIA, Nathalia Coelho (2024)
Aim: To compare the pattern of the main and secondary sleep episodes and physical activity between summer and winter in Antarctica. Materials and methods: Descriptive longitudinal study, carried out at the Comandante Ferraz Antarctic Station, with a sample of 11 volunteers. To evaluate sleep variables, naps and physical activity, participants wore an ActTrust wristwatch-shaped accelerometer (actigraph) on their non-dominant hand, for at least 3 days, in January (summer), May and August. (winter). Results: There was an increase in the duration of sleep during the main episode (p = 0.004), a delay in waking up (p = 0.002) and maintenance of sleep efficiency (p = 0.135) throughout the year, without changes in the pattern of secondary episodes. There was also a reduction in M10AF of physical activity during the Antarctic winter (p <0.001). Conclusion: The prolonged stay at the Comandante Ferraz Antarctic Station resulted in an increase in sleeping time and a delay in waking up in winter, with the maintenance of sleep quality, indicating a need to increase the duration of sleep for recovery. However, there was no impact on secondary sleep episodes (naps). The smaller amount of physical activity M10, in winter, was not sufficient to harm the quality of sleep or the pattern of secondary episodes (naps).